2019
DOI: 10.1186/s13023-019-1036-2
|View full text |Cite
|
Sign up to set email alerts
|

Betaine anhydrous in homocystinuria: results from the RoCH registry

Abstract: BackgroundThe Registry of Adult and Paediatric Patients Treated with Cystadane® – Homocystinuria (RoCH) is a non-interventional, observational, multi-centre, post-authorization safety study that aimed to identify safety of betaine anhydrous (Cystadane®) in the treatment of patients with inborn errors of homocysteine metabolism (homocystinuria) in order to minimise the treatment associated risks and establish better knowledge on its clinical use. The registry included patients of all ages with homocystinuria wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 27 publications
0
27
0
1
Order By: Relevance
“…Also, when betaine was administrated in partially hepatectomized rats, it promoted liver regeneration whereby the liver regained its original weight in 7 days after surgery [ 14 ]. Alongside, it has exhibited great therapeutic potential in clinical trials for non-alcoholic steatohepatitis [ 15 ] and homocystinuria [ 16 ]. Generally, betaine has shown hepatoprotective properties against liver injury by enhancing antioxidant mechanisms and adipose tissue function, while reducing oxidative stress, endoplasmic stress, liver fibrosis and necrosis [ 17 ].…”
Section: Contextual Therapeutic Potential Of Betainementioning
confidence: 99%
See 1 more Smart Citation
“…Also, when betaine was administrated in partially hepatectomized rats, it promoted liver regeneration whereby the liver regained its original weight in 7 days after surgery [ 14 ]. Alongside, it has exhibited great therapeutic potential in clinical trials for non-alcoholic steatohepatitis [ 15 ] and homocystinuria [ 16 ]. Generally, betaine has shown hepatoprotective properties against liver injury by enhancing antioxidant mechanisms and adipose tissue function, while reducing oxidative stress, endoplasmic stress, liver fibrosis and necrosis [ 17 ].…”
Section: Contextual Therapeutic Potential Of Betainementioning
confidence: 99%
“…Exposure of 4 g/day for 6 months showed no adverse effects on platelet counts in human. Exposure of 0.4 g/day betaine in addition to the endogenous exposure is considered safe for human [ 50 ] Clinical trials Oral, 1,3,6 g single doses mixed with orange juice after overnight fast [ 51 ] Oral, 3 g/day for 1 month [ 9 ] Oral, 10 g, twice a day, probably for 12 months [ 13 ] Oral, 20 g/day for 12 months [ 52 ] 3–9 g/day for different conditions for a mean of 7.4 ± 4.3 years [ 16 ] Oral, betaine glucoronate in combination with diethanolamine glucuronate and nicotinamide ascorbate for 8 weeks [ 53 ] Oral, 20 g/day in 2 divided doses for 12 months [ 54 ] Oral, 10 g (anhydrous betaine) twice a day for 12 months [ 55 ] Animal experiments Piglets: 20 g/kg feed (2% betaine in diet) for 6 weeks [ 50 ] Rats: ethanol with 1% betaine for 6 months [ 7 ] Rats: 10 and 50 mg/kg i.p for three consecutive days [ 17 ] Rats: ethanol containing water with betaine (1% w/v) for 6 months [ 18 ] Rats: betaine 0.4 g/kg/day intragastrically post 12 weeks of high-fat diet from weeks 13–16 [ 19 ] Rats: ethanol with betaine (1% w/v; 10 mg/mL) for 4–5 weeks [ 23 ] Rats: ethanol with 1% betaine for 4 weeks [ 28 ] ...…”
Section: Betaine Restores Alcohol-induced Reduction In Vldl Synthesis...mentioning
confidence: 99%
“…The efficacy of Bet in lowering tHcy diminished significantly over time in HO mice [ 26 ], which was later found to be alleviated by taurine treatment, which induced Bet-repressed expression of BHMT [ 27 ]. However, the long-term efficacy of Bet in HCU patients does not seem to be compromised [ 28 ]. Our studies showed that OT-58 provided additional benefit in correcting metabolic balance in HO mice over Bet supplementation alone and successfully competed with Bet for Hcy substrate.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we approached clinical metabolic specialists who participate in a large international email‐based discussion forum (Metab‐L, A mailing‐list on Inborn Errors of Metabolism, http://www.metab-l.de) and the sponsor of the European post‐authorization safety study for betaine to identify potential further unpublished cases. This project was endorsed by the European network for Homocystinurias and Remethylation Disorders (E‐HOD).…”
Section: Methodsmentioning
confidence: 99%